Desempeño laboral de los ejecutivos de servicio transaccional de Banco Pichincha agencia Babahoyo - Rosado Cevallos, Kleber Ricardo (2020)
The research on the job performance of Transactional Executives has determined that the professional who works in the Cashier Area has problems in developing their job skills, because when the institution trains through the cashier school, only It is carried out virtually and not from practice, which implies adaptation problems or attending to the bank's clients with agility and in a timely manner; For this reason, the objective of the research is to analyze the situations that influence the job performance of the Transactional Services Executive, in addition, it is important to highlight that the inadequate development of work activities in an area of massive user congestion implies that the service process is slow and the institutional image of the financial institution is affected. The methodology that the case study has is made up of descriptive research, inductive method, survey technique and a questionnaire of questions as instruments, necessary tools to obtain relevant information about the research premise. The results of the investigation are linked by the professional skill of the cashier, errors in reconciliation of income and expenses, negative factors that denote weak work performance.